Reconstructive Microsurgery: Challenges and New Perspectives (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The subspecialty of reconstructive microsurgery utilizes microsurgical techniques to allow surgeons to operate on the smallest of structures, including vessels, lymphatics, and nerves. Traditionally, these procedures have been used by microsurgeons to reconstruct complex tissue defects through the use of free tissue transfer, which involves the transfer of tissue (free flaps) between distant anatomic sites on the body. As the field has advanced, microsurgical techniques have been applied to even smaller structures, opening the door for new procedures, such as lymphatic reconstruction in the management of lymphedema and new types of free flaps. In addition, refinement in the technique has allowed microsurgeons to now perform many of these procedures with minimal donor site morbidity. Lastly, trends in plastic and reconstructive surgery have also resulted in the more widespread use of other applications for microsurgery, such as gender-affirming surgery and vascularized tissue allotransplantation. In this Special Issue, the latest research in reconstructive microsurgery is presented, including in the areas of microsurgical technique, robotic microsurgery, and program development.